System Design Estimation of Cost for Laying Chicken Feed Formulation using Web-Based Square Pearson Method - Anton Setiawan Honggowibowo; Astika Ayuningtyas; Yuliani Indrianingsih (UIN Sunan Kalijaga Yogyakarta, 2020)
Feed is one important element that needs to be considered in the livestock business, one of which is laying hens. The type and amount of feed will affect the nutrients obtained, these nutrients will affect the ability to produce eggs. One way to produce feed that contains optimal nutrition is done by mixing various types of feed ingredients such as corn, bran, cake, soybeans, concentrate and so on into one right composition. Expenditures for the purchase of feed are also among the highest expenses in any livestock business and therefore need to be regulated in such a way as to provide optimal benefits. The square pearson method is a method of determining the formulation of feed which on one hand contains complete nutrients, on the other hand is economically inexpensive and easily obtained so that it can provide benefits. The results of this study produce a system that can estimate the cost of calculating web-based laying hens feed formulations.